Simulasi Numerik Gerakan Lengas Tak Jenuh dalam Tanah pada Sistem Irigasi Tetes - Muhammad Aqil; Sigit Supadmo; Budi Rahardjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
The soil of coastal plain is characterized by sandy soil texture, salinity problem, low water capacity, high oercolation rate and high soil temperature during day time. Due to those constraints, therefore much water is needed to be favorable to plant growth. Objective of the research is dealing with the application of numberical method to simulate heat and mass flow of water which is affected by soil moisture availability. A core of soil sample with size 50 cm x 50 cm x50 cm is used as a physical model. The research has been schedule from 1997 to 1998. Under high initial moisture content the simulation shows that there is similarity between predicted and observed value of soil moisture content with the correlation value more that 90% (t-test value 95%). However, the simulation is under estimate for low initial moisture content and high temperature. For the model applications, the factor's which influence on moisture movement in the soil was collected and rearranged in exponential equation: θv = 103,469. Qirr 0.015. T 0.061. t 0.235. x -0.161. z -2.842. From the model found that to keep soil moisture content in favorable condition (θv = 0,1 cm3/cm3), the discharge design of drip irrigation needed was 3.2 cm3/sec with 2 hours duration of irrigation. The discharge designed based on water needed for evaporation and heat flushing so that moisture in the root zone was maintained.